Laparoscopic injury of the obturator nerve during fertility-sparing procedure for cervical cancer - Ricciardi Enzo (World Journal of Surgical Oncology, 2012)
Abstract Background Intraoperative injury of the obturator nerve has rarely been reported in patients with gynecological malignancies undergoing extensive radical surgeries. Irreversible damage of this nerve causes thigh paresthesia and claudication. Intraoperative repair may be done by end-to-end anastomosis or grafting when achieving tension-free anastomosis is not possible. Case presentation A 28-year-old woman with stage IB cervical cancer underwent fertility–sparing surgery, including conization and bilateral pelvic lymphadenectomy. The left obturator nerve was damaged intraoperatively during pelvic dissection. Conclusion Immediate laparoscopic repair was successful and there was no functional deficit in the left thigh for six months postoperatively.